2011
DOI: 10.1016/j.jjcc.2010.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Associations of positive T wave in lead aVR with hemodynamic, coronary, and left ventricular angiographic findings in anterior wall old myocardial infarction

Abstract: The positive T wave in lead aVR is related to severely reduced cardiac function, with an LAD wrapping the apex, in anterior wall old MI. Further studies are needed to clarify whether the positive T wave in lead aVR is associated with an adverse outcome in patients with anterior wall old MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…We found subjects with a positive/flat T wave in aVR to have a greater burden of classical cardiovascular risk factors (i.e. older age, diabetes, hypertension, low LVEF, and previous MI), which is consistent with published studies [1722]. However, when looking at the subgroup with normal LVEF (≥ 50%), normal QTc (≤ 450ms), and without diabetes, a positive/flat T wave in aVR still remained significantly associated with SCD, suggesting that this ECG finding may have a specific association with ventricular arrhythmias.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found subjects with a positive/flat T wave in aVR to have a greater burden of classical cardiovascular risk factors (i.e. older age, diabetes, hypertension, low LVEF, and previous MI), which is consistent with published studies [1722]. However, when looking at the subgroup with normal LVEF (≥ 50%), normal QTc (≤ 450ms), and without diabetes, a positive/flat T wave in aVR still remained significantly associated with SCD, suggesting that this ECG finding may have a specific association with ventricular arrhythmias.…”
Section: Discussionsupporting
confidence: 92%
“…It has also been postulated that ischemia in the anterior and inferior wall may cause spatial directional changes in the repolarization vector leading to less negative or positive T waves in lead aVR [15]. One study looking at coronary angiography data in patients with old anterior wall myocardial infarction (MI) found those with a positive T wave in lead aVR had greater likelihood of a longer left anterior descending artery (LAD), ≥ 75% stenosis of the LAD and multi-vessel disease compared to those with negative T wave (although the latter two were not statistically significant), supporting ischemia as one cause for repolarization abnormalities leading to T wave positivity in lead aVR [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms explaining why an upright aVRT occurs on the ECG are not identified, it has been suggested that a long left anterior descending artery and multivessel disease, in both cases, along with an ischemically injured myocardium in these areas of the heart, would be expected to make a normally negative T-wave inverted and lead to a flat or positive T-wave [20,21,22,23]. Ayhan et al [22] suggested that a positive T-wave in lead aVR in patients with anterior ST segment elevation myocardial infarction undergoing primary PCI may be caused by multivessel disease, and Joki et al [4] evaluated coronary angiography in incident hemodialysis patients and showed that more than half of the patients had significant CAD; it should be noted that >70% of CAD patients had multivessel disease.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies [23,24] have investigated the significance of T-wave positivity in lead aVR in prior MI. We [23] examined 122 patients with anterior wall prior MI and found that 20 patients with a T wave (≥ 0.1 mV) in lead aVR had higher pulmonary arterial, pulmonary capillary wedge, and LV end-diastolic pressures, a lower cardiac index, and a lower LV ejection fraction than 102 patients without such a T wave in lead aVR.…”
Section: T-wave Abnormality In Lead Avrmentioning
confidence: 99%
“…We [23] examined 122 patients with anterior wall prior MI and found that 20 patients with a T wave (≥ 0.1 mV) in lead aVR had higher pulmonary arterial, pulmonary capillary wedge, and LV end-diastolic pressures, a lower cardiac index, and a lower LV ejection fraction than 102 patients without such a T wave in lead aVR. The prevalence of a long LAD was significantly higher in the former group than in the latter group (60% vs 30.4%, P = 0.01), and none of the former group had an LAD that did not reach the apex.…”
Section: T-wave Abnormality In Lead Avrmentioning
confidence: 99%